Religious Feelings and Motivation of Adolescents in Learning Al-Qur'an: A Case Study at Pondok Pesantren Al-Hasan Ciamis - Siti Shofiyah; Ummah Karimah; Dede Alfiyah Nurhovivah; Rusjdy Sjakyakirti Arifin; Ahmad Yunus (IAIN Padangsidimpuan, 2022)
Every individual who reads the Qur'an closely relates to the rituals of Muslims. Included in the discussion are students in Islamic boarding schools (Pondok Pesantren). Over time, more relevant and exciting methods of reading the Qur'an emerged, including the Iqro method, the Tsaqifa method, and the Qira'ati method. However, not all students have good religious feelings and motivation to learn to read Al-Qoran, especially teenage students. The purpose of this study was to determine the religious feelings and motivations of Qiro'ati students at Pondok Pesantren Al-Hasan Ciamis. This study used a qualitative approach using interviews with teachers and students at Al-Hasan Islamic Boarding School Ciamis. Data analysis was carried out by reducing, analyzing, and drawing conclusions from the data obtained by the researcher. The results of this study are that the students of Al-Hasan Islamic Boarding School Ciamis have unstable religious feelings but have strong religious motivation because of the desire to satisfy curiosity and are influenced by groups of friends.